Transcutaneous measurement of glomerular filtration rate in rodents - Daniele, Cristina; Nardozi, Daniela; Torelli, Angelo; Khan, Arif ul Maula; Gretz, Norbert (Diabetic nephropathy, 2020)
Glomerular filtration rate (GFR) is considered the gold standard to test kidney function. However, the serial blood and/or urine sample collection required for the calculation of the GFR is stressful for the animal and time consuming for the experimenter. Here, we describe a transcutaneous assessment of renal function in conscious animals that does not require plasma or urine sampling and/or deep anesthesia. For the measurement, we use a near-infrared (NIR) device that records the excretion kinetic of the renal marker ABZWCY-HPβCD. ABZWCY-HPβCD is a new hydrophilic, stable, and nontoxic NIR fluorescent agent that can be used as a renal marker as it is filtrated and completely excreted through the kidneys into the urine without reabsorption or secretion and without accumulation in the skin. The data recorded in the device are then analyzed with “GFRmeasure,” an open-source, freely downloadable, and user-friendly software.
Online veröffentlicht: 8. November 2019
Gesehen am 13.08.2025